1992
DOI: 10.1016/0735-1097(92)90054-q
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and limitations of exercise echocardiography in a routine clinical setting

Abstract: Despite the high reported accuracy of exercise echocardiography in the detection of coronary artery disease, factors that compromise its sensitivity and specificity are less clear. This study examined the results of 179 post-treadmill stress echocardiograms in 150 consecutive patients who also underwent cardiac catheterization and in 29 normal persons at low risk for coronary artery disease. Of 114 patients who had significant coronary stenoses at angiography, 96 had an abnormal exercise echocardiogram (overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
95
3
5

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 359 publications
(105 citation statements)
references
References 36 publications
2
95
3
5
Order By: Relevance
“…Nevertheless, ExE has a number of limitations, including its dependence on the provocation of wall-motion abnormalities (WMAs) for the diagnosis of ischemia, reliance on qualitative wall-motion scoring, 2 and underestimation of the extent of CAD. 1,3 Radionuclide perfusion imaging appears to be more accurate for determining the extent of CAD, 3 probably because hypoperfusion occurs before WMAs are evident in the ischemic cascade. 4 Myocardial contrast echocardiography (MCE) enables assessment of myocardial perfusion by ultrasound.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, ExE has a number of limitations, including its dependence on the provocation of wall-motion abnormalities (WMAs) for the diagnosis of ischemia, reliance on qualitative wall-motion scoring, 2 and underestimation of the extent of CAD. 1,3 Radionuclide perfusion imaging appears to be more accurate for determining the extent of CAD, 3 probably because hypoperfusion occurs before WMAs are evident in the ischemic cascade. 4 Myocardial contrast echocardiography (MCE) enables assessment of myocardial perfusion by ultrasound.…”
mentioning
confidence: 99%
“…xercise echocardiography (ExE) is an established clinical tool with a high sensitivity and specificity 1 for the diagnosis of coronary artery disease (CAD). Nevertheless, ExE has a number of limitations, including its dependence on the provocation of wall-motion abnormalities (WMAs) for the diagnosis of ischemia, reliance on qualitative wall-motion scoring, 2 and underestimation of the extent of CAD.…”
mentioning
confidence: 99%
“…34 A false-negative response on EE among patients with significant coronary artery stenosis correlates well with the performance of a submaximal exercise (<85% of the maximal agepredicted heart rate), single-vessel disease, and moderate stenoses from 50% to 70%. 7 In the current report, the mean maximal heart rate achieved among patients with a negative response on EE was 87% of the maximal predicted heart rate.…”
Section: Advantages and Limitationsmentioning
confidence: 96%
“…3 Exercise echocardiography (EE) is an accepted tool for the assessment of the functional significance of coronary obstructions among patients with coronary artery disease (CAD). [4][5][6][7][8] In previous reports, the classification of CAD has been mostly semiquantitative, assessed by visual analysis, or based on predetermined cutoff values of angiographic parameters. 4,5,[7][8][9][10] A few studies that used quantitative analysis of coronary stenosis have demonstrated the diagnostic accuracy of EE for the detection of significant CAD in selected patients with single-vessel disease and normal echocardiograms at rest.…”
mentioning
confidence: 99%
See 1 more Smart Citation